2011
DOI: 10.1117/12.893691
|View full text |Cite
|
Sign up to set email alerts
|

Non-phosphor white LED light source for interferometry

Abstract: Solid state light sources are replacing a tungsten filament based bulbs in Scanning White Light Interferometers. White LEDs generate little heat, feature short switching times, and have long lifetimes. Phosphor-based white LEDs produce a wide spectrum but have two separate peaks which cause interferogram ringing. This makes measuring multi layered structures difficult and may degrade measurement precision even when measuring a single reflecting surface. Most non phosphor white LEDs exhibit a non Gaussian spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 7 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Other than the designed and the undesired spectral variations mentioned above, the intensity spectrum of the dual wavelength white LED can vary depending on its operating condition [5,15] and optical degradation [16,17]. For example, (1) when the white LED is being pulsed at high frequency, the relative intensity of the blue and yellow light components changes [5], and (2) the center wavelength of blue light shifts by 7 nm when the duty cycle in pulsing mode is changed from 1% to 10% [15].…”
Section: Dual Wavelength White Ledmentioning
confidence: 99%
See 3 more Smart Citations
“…Other than the designed and the undesired spectral variations mentioned above, the intensity spectrum of the dual wavelength white LED can vary depending on its operating condition [5,15] and optical degradation [16,17]. For example, (1) when the white LED is being pulsed at high frequency, the relative intensity of the blue and yellow light components changes [5], and (2) the center wavelength of blue light shifts by 7 nm when the duty cycle in pulsing mode is changed from 1% to 10% [15].…”
Section: Dual Wavelength White Ledmentioning
confidence: 99%
“…For example, (1) when the white LED is being pulsed at high frequency, the relative intensity of the blue and yellow light components changes [5], and (2) the center wavelength of blue light shifts by 7 nm when the duty cycle in pulsing mode is changed from 1% to 10% [15].…”
Section: Dual Wavelength White Ledmentioning
confidence: 99%
See 2 more Smart Citations
“…[88] and is expected to last longer [89], [90]. Other than a achieving high modulation frequency, Heikkinen et al [61] also found that there is spectral variation at different pulsing frequency. As shown in Figure 2-22, it is found that the ratio between the blue and yellow lights of the non phosphor-based white LED changes with pulsing frequency and the wavelength of the yellow light also increases as the pulsing frequency increases.…”
Section: Hardware Related Researchmentioning
confidence: 99%